2021
DOI: 10.1108/bpmj-12-2020-0573
|View full text |Cite
|
Sign up to set email alerts
|

Smart supply chain and firm performance: the role of digital technologies

Abstract: PurposeThis study aims to explore the impact of digital transformation on firm performance with the help of smart technologies.Design/methodology/approachThis study used a valid and well-structured survey to collect data from 460 respondents from 150 Small and medium-sized enterprises (SMEs) in Saudi Arabia. In order to analyze this data, SmartPLS software was used.FindingsThe empirical results of this study found that the digital transformation has no significant direct impact on firm performance. Therefore, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 81 publications
(139 reference statements)
2
57
0
Order By: Relevance
“…A meta-analysis by Sabherwal and Jeyaraj (2015) shows that IT adoption can strengthen the relationship between IT investment and the business value of IT. Moreover, smart technology plays an important role in establishing the link between digital transformation and firm performance (AlMulhim, 2021). On the other hand, enterprises need to develop their IT competency to enhance their overall performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A meta-analysis by Sabherwal and Jeyaraj (2015) shows that IT adoption can strengthen the relationship between IT investment and the business value of IT. Moreover, smart technology plays an important role in establishing the link between digital transformation and firm performance (AlMulhim, 2021). On the other hand, enterprises need to develop their IT competency to enhance their overall performance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Conversely, the empirical results revealed that DT had no significant direct effect on firm performance; however, it had an indirect effect (smart technologies are mediators). In addition, the results showed that DT directly affected the development and usability of smart technologies applied to improve organizational performance [84]. Furthermore, DT had a significant positive indirect effect on HPO (β = 0.127, t = 2.376, and p = 0.009), and OSI functioned as the partial mediator of this relationship.…”
Section: Hypothesis Testingmentioning
confidence: 91%
“…Exploitative ISU is defined as the operational use of IS resources to support the goals of firms and their supply chains. By leveraging on existing IS, firms expand their IS capabilities in serving supply chain partners (AlMulhim, 2021; Frank et al, 2019). Information system is entrenched in organizational process through technology and sharing of technology (Frank et al, 2019).…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…The use of IS justifies long-term investments, and the analysis of markets and competitors to inform firms’ decisions (Javornik & Mandelli, 2012). This, however, underscores the importance of the integration of information systems with supply chain management (AlMulhim, 2021). Similarly, Frank et al (2019) revealed a significant manufacturing performance in organization when supply chain process is integrated with innovative process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation